2017
DOI: 10.1002/lary.26703
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative anticoagulation after free flap reconstruction for head and neck cancer: A systematic review

Abstract: There is not adequate evidence to develop a standardized anticoagulation protocol for head and neck free flap procedures. Comparable flap complications were reported between all the employed anticoagulation methods studied, though significant variability in study design among articles existed. Prospective, randomized studies are warranted to determine the optimal postoperative anticoagulation regimen following free tissue transfer of the head and neck. Laryngoscope, 128:412-421, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 57 publications
(109 reference statements)
2
55
0
Order By: Relevance
“…Anticoagulation is primarily aimed at preventing venous thrombosis at or near the microvascular anastomosis, as compromised venous outflow is a common contributor to free flap failure and may require return to the OR for anastomotic revision. Many surgeons choose an anticoagulation regimen based on anecdotal evidence and personal experience, and studies have found comparable free flap outcomes in a wide variety of regimens . Our study shows the variable use of heparin and Lovenox, though there is relatively widespread adoption of postoperative aspirin (40.3% 81 mg, 48.4% 325 mg) and abandonment of dextran (Fig.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Anticoagulation is primarily aimed at preventing venous thrombosis at or near the microvascular anastomosis, as compromised venous outflow is a common contributor to free flap failure and may require return to the OR for anastomotic revision. Many surgeons choose an anticoagulation regimen based on anecdotal evidence and personal experience, and studies have found comparable free flap outcomes in a wide variety of regimens . Our study shows the variable use of heparin and Lovenox, though there is relatively widespread adoption of postoperative aspirin (40.3% 81 mg, 48.4% 325 mg) and abandonment of dextran (Fig.…”
Section: Discussionmentioning
confidence: 77%
“…Many modalities of flap monitoring exist, as well as many institutional schema regarding the optimal timing and responsible providers for flap checks . Anesthetic/sedation plans, appropriate postoperative level of care, duration of postoperative antibiotics, and anticoagulation plans have all been studied, yet no consensus exists for these aspects of patient care following MFTT . Furthermore, perioperative care regimens have not been reliably associated with measures of overall free flap success or complication rates .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chien et al reported that 96% of reconstructive surgeons utilize some form of anticoagulation regimen to manage free tissue transfer patients [24]. Various anticoagulants that are administered include aspirin, heparin, low molecular weight heparin, and dextran [23]. The patient in this report received daily aspirin 325 mg. We suggest that if hemophilic patients have their factor deficiencies adequately replenished, they can be treated the same as a nonhemophilic patient with regard to antiplatelet therapy.…”
Section: Discussionmentioning
confidence: 85%
“…Do not draw through a heparinized IV. If factor IX level < 50%, give 100 units/kg Mononine and then continue 25 units/kg every 12 hours (vii) Discharge the patient with peripheral IV in place so that he can administer factor at home Home schedule: [23]. Chien et al reported that 96% of reconstructive surgeons utilize some form of anticoagulation regimen to manage free tissue transfer patients [24].…”
Section: Discussionmentioning
confidence: 99%